A comparative study of participatory and household risk assessments and an investigation into the impact of a participatory risk assessment to effect change: case study: Section D, Sweet Home farm, Cape Town - Arthern, Peter J (Department of Environmental and Geographical Science, 2014)
Includes bibliographical references (leaves 68-80).